(untitled) (Scientific journal of the Fergana State University, 2023)
The article describes the amount of macroelements in meadow-oasis soils formed in the climatic conditions of Fergana region. In the research, the chemical element composition of meadow-oasis soils and Indigofera tinctoria L. plant was irradiated with a neutron stream using the neutron activation method, and their amounts were determined based on the half-life of chemical elements. Macroelement amounts were compared to lithosphere and soil clark. The amounts of chemical elements Na, K, Ca, Fe and Ba in the composition of the plant Indigofera tinctoria L. grown in meadow-oasis soil conditions were determined and their importance was studied.